2008
DOI: 10.1016/j.jacc.2008.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Interstitial Alterations in Remodeling Myocardium After Myocardial Infarction

Abstract: Radiolabeled CRIP allows for noninvasive visualization of interstitial alterations during cardiac remodeling, and is responsive to antiangiotensin treatment. If proven clinically feasible, such a strategy would help identify post-MI patients likely to develop heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 37 publications
8
117
0
2
Order By: Relevance
“…Even after 4 mo, the focal accumulation remained at a higher level than in the sham group. The similar distribution pattern of arginine-glycineaspartic acid--based tracer in models of myocardial ischemia has been observed by other groups (40,41). In contrast, 18 F-FBEM-Cys 40 -exendin-4 showed a dramatically different uptake pattern.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Even after 4 mo, the focal accumulation remained at a higher level than in the sham group. The similar distribution pattern of arginine-glycineaspartic acid--based tracer in models of myocardial ischemia has been observed by other groups (40,41). In contrast, 18 F-FBEM-Cys 40 -exendin-4 showed a dramatically different uptake pattern.…”
Section: Discussionsupporting
confidence: 83%
“…The fused images clearly showed localization of 18 F-FBEM-Cys 40 -exendin-4 within the myocardium at 1 d after MI/R. 18 F-FBEM-cys 40 -exendin-4 signal detected with PET corresponded to anterolateral myocardium and was clearly separated from the intercostal muscle layer.…”
Section: Image Colocalizationmentioning
confidence: 92%
“…Myocardial collagen fibers are consisted of type I, type II and type V fibrillar collagen. These types of collagen are synthesized by fibroblasts and account for about 90% of all the collagen within the heart [19][20][21]. Interstitial collagen networks support the architecture and the arrangement of the cardiomyocytes during the cardiac cycle and the improves force transferred to the ventricular chambers.…”
Section: Discussionmentioning
confidence: 99%
“…14 Preclinical studies have shown feasibility of visualizing avb 3 integrin 15,16 (on myofibroblasts), angiotensin-converting enzyme (ACE), 17 angiotensin II receptor type 1 (AT1), 18 and coagulation factor XIII. 19 Although initial small scale clinical pilot studies have been performed for some of these tracers, [20][21][22] no definitive studies have been performed.…”
Section: See Related Article Pp 1114-1123mentioning
confidence: 99%